The Effectiveness Chewing gum versus Cryotherapy on Salivary Volume among Patient with Head and Neck Cancer undergoing Radiotherapy - Dwi Uswatun Sholikhah; I Ketut Sudiana; Ninuk Dian Kurniawati (Universitas Airlangga, 2020)
Introduction: Hyposalivation is a common problem experienced by head and neck (H&N) cancer patients undergoing radiotherapy. Hyposalivation can cause negative effects on the physical aspects of making oral mucositis, pain during eating and talking as well as psychological effects that cause feeling of discomfort sadness and, ultimately, depression. Many nonpharmacological interventions can be done for hyposalivation that occur in patients, among which are chewing gum and cryotherapy because they are easy to do, easy to access, inexpensive and have minimal side effects. However, the effectiveness of these interventions is not yet clear. Hence, this study is aimed to determine the effectiveness of chewing gum versus cryotherapy to increase salivary volume in H&N cancer patients undergoing radiotherapy.Methods: A quasi-experimental time series group design to determine the most effective time to influence the increase in salivary volume. This research was conducted on 36 respondents H&N cancer undergoing radiotherapy with four times measurement are pretest-posttest on the 3rd, 5th, and 7th day of intervention between February and March 2020. Subjects were chosen using consecutive sampling. Chewing gum group will chew gum six (6) pieces/day and cryotherapy group will suck on ice cubes five (5) minutes before and after radiotherapy. The spitting method was used to collect saliva and the data were analyzed using General Linear Model-Repeated Measure (GLMRM).Results: Chewing gum is more effective to increase salivary volume than cryotherapy. The GLMRM within subjects at four (4) times measurement showed a significant difference between chewing gum and cryotherapy group with p value <0.05 on the 7th day. Subjects in the chewing gum group had better salivary volume increment than cryotherapy group.Conclusion: This study showed that chewing gum is more effective to increase salivary volume on patient H&N cancer undergoing radiotherapy because chewing gum has higher salivary volume increment than cryotherapy groups